(untitled) (Plant Tissue Culture and Biotechnology, 2020)
The chances of shoot-regeneration from embryo culture of Morinda citrifolia L. seeds was investigated. Germination on different strengths of MS and control (Sterile distilled water) started by two weeks after inoculation (WAI). At 6 WAI, 90% of the embryo had germinated from 25% MS followed by 80% in control, 70% from 50% MS and 40% each from 100 and 75% MS. Similarly, the same MS media strengths with basal application of 2.0/1.0 mg/l BAP/Kn affected the growth of regenerated Noni-plantlets. The longest shoot length (3.46 cm) and the number of nodes (1.75) were obtained from 75% MS while the highest number of leaves (7.25) was obtained in 100% MS between 4 and 12 WAI. The lowest value for these parameters were observed in 25% MS. This showed that mature zygotic embryo is good explant for the establishment of highly viable and re-generable plantlets of Noni. Plant Tissue Cult. & Biotech. 30(2): 199-207, 2020 (December)